The effects of dietary organic or inorganic selenium in rainbow trout (Oncorhynchus mykiss) under crowding conditions - Kucukbay, F. Z.; Yazlak, H.; Karaca, I.; Şahin, Nurhan.; Tuzcu, M.; Cakmak, M. N.; Şahin, Kazım (Wiley, 2009)
In the present study, the effects of different sources of selenium (Se; sodium selenite or selenomethionine) supplementation on the growth and serum concentrations of oxidative stress markers [malondialdehyde (MDA), 8-isoprostane, glutathione peroxidase (GSH-Px) activity] and muscle Se, MDA and heat shock protein 70 (Hsp70) levels in rainbow trouts were evaluated. The fish (n = 360; 0 + years old) with initial average weight of 20 +/- 0.8 g were randomly assigned to 12 treatment groups consisting of 3 replicates of 10 fish each in a 2 x 2 x 3 factorial arrangement of treatments (stocking densities, Se sources, Se levels). The fish were kept at low (25 kg m-3) or high (100 kg m-3) stocking densities and fed a basal (control) diet or the basal diet supplemented with either 0.15 or 0.30 mg of Se kg-1 of diet from two different forms: sodium selenite or selenomethionine. High stocking density decreased weight gain, feed intake and feed conversion ratio (FCR) when basal diet was fed (P = 0.001). A linear increase in feed intake and weight gain and improvement in FCR were found in sodium selenite (P = 0.01)- or selenomethionine (P = 0.001)-supplemented fish reared under crowding conditions. Serum and muscle Se levels and serum GSH-Px activity increased (P = 0.001) linearly, whereas serum and muscle MDA concentrations and serum 8-isoprostane decreased linearly as dietary sodium selenite (P = 0.01) or selenomethionine (P = 0.001) supplementation increased. Selenomethionine and sodium selenite supplementation decreased Hsp70 in the muscle of fish reared under crowding conditions (P < 0.05). Supplementation with Se improved growth and antioxidant status of fish and the effects of selenomethionine were relatively greater than sodium selenite in the crowded groups. Results suggest that crowding conditions cause significant detrimental effects in rainbow trout indicated by increased oxidative stress, reduced feed intake and body weight gain. It also indicates that dietary Se supplementation offers a feasible way of reducing the losses in performance of rainbow trout reared under crowding conditions. Selenomethionine seems to be more effective than sodium selenite and the higer dose in the present study also seems to be more effective than the lower dose.
Keywords: GSH-Px; Hsp70; MDA; rainbow trout; selenium; stocking density